1974
DOI: 10.1203/00006450-197402000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Findings in Acrodermatitis Enteropathica

Abstract: ExtractDuodenal biopsies from patients with acrodermatitis enteropathica were examined by electron microscopy and dissecting microscopy. T h e ultrastructural studies revealed characteristic inclusions in Paneth cells with a maximum length of 7 pm. These findings were constant in four different patients. A follow-up study in one patient showed the same alterations before and after treatment. SpeculationT h e biochemical defect of acrodermatitis enteropathica is unknown and, therefore, typical ultrastructural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

1980
1980
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 3 publications
1
15
0
3
Order By: Relevance
“…Some reports have suggested that the inclusion is similar to the cytoplasmic inclusions which are seen in Paneth cells of the bowel in cases of acrodermatitis enteropathica or experimentally induced zinc deficiency [19,24]. However, the fibrillary-like structure of the inclusions did not form a bundle.…”
Section: Discussionmentioning
confidence: 92%
“…Some reports have suggested that the inclusion is similar to the cytoplasmic inclusions which are seen in Paneth cells of the bowel in cases of acrodermatitis enteropathica or experimentally induced zinc deficiency [19,24]. However, the fibrillary-like structure of the inclusions did not form a bundle.…”
Section: Discussionmentioning
confidence: 92%
“…The aetiology of the watery diarrhoea is unknown; it may represent an intestinal infection or impaired mucosal function. Several intestinal mucosal lesions have been reported; these include a zinc responsive small intestinal villous atrophy (Kelly et al, 1976), and inclusion bodies and abnormal intracellular organetles in the paneth cells and the enterocytes (Lombeck et al, 1974;Braun et al, 1976;Elm~ et aI., 1982;Neldner et at., 1974). These changes are probably secondary to but not peculiar to zinc deficiency (Baudon et al, 1978;Elmes et al, 1982).…”
Section: Aggettmentioning
confidence: 97%
“…In zinc-deficient rats, absorption of olive oil and triolein was found to be impaired, while normal TG digestion and therefore no steatorrhoea were present [26]. The resynthesised TG were found to accumulate in the intestinal mucosa as lipid droplets, 24 ttm in size, similar to the Paneth cell granulae found in AE [27]. Like the plasma FA changes in our patients, the inclusion bodies in intestinal epithelial cells receded after zinc supplementation [22].…”
Section: Discussionmentioning
confidence: 85%
“…Electron microscopy of a small bowel biopsy revealed pleomorphic Paneth cell granulae characteristic for AE [27]. Oral therapy with zinc sulfate, 3 x 50 mg/day, was started at the age of 6 months and a body weight of 4.4 kg, while the child was fed with Alfar6 and small amounts of breast milk.…”
Section: Case Reportmentioning
confidence: 99%